The first Russian newspaper in Shanghai (1918–1921) - Sun Yizhi (Омский научный вестник: Серия "Общество. История. Современность")
This paper deals with the history of first Russian newspaper in Shanghai: Russian section of «Shanghai Gazette». With a detailed analysis of this newspaper, I have succeeded in identifying five editorial staffs of the Russian section: the first SocialRevolutionary staff, the Bolshevik staff, the White Army staff, the second SocialRevolutionary staff and the Monarchic staff. The author concluded that the editorial staffs of Russian section don’t follow a policy of the Editor-in-chief Chen Youren, colleague of Dr. Sun Yat-sen. At that time the members of Kuomintang couldn’t clearly know about the political situation of Russia, and from 1918 to 1920 there were very few people in China who knew the Russian and could translate Russian articles into Chinese. This is why the Editor-in-chief Chen Youren hadn’t notice that there were a large number of anti-Bolshevik elements in his Kuomintang newspaper.